Flow-cycled versus time-cycled sIPPV in preterm babies with RDS: a breath-to-breath randomised cross-over trial. Issue 6 (1st July 2009) - De Luca, D; Conti, G; Piastra, M; Paolillo, P M
Abstract : Objectives: Few data exist about patient-triggered ventilation techniques in neonatal critical care. Our aim was to compare pressure-limited synchronised intermittent positive pressure (or assist/control) ventilation (sIPPV) in the classical time-cycled (TC-sIPPV) mode against flow-cycled (FC-sIPPV) modality. In this latter, typical sIPPV full respiratory support is provided but both the initiation and the end of inflation are determined by the infant's spontaneous respiratory efforts by using airway flow changes. Setting: A third-level neonatal intensive care unit. Patients and intervention: Ten preterm babies (<32 weeks' gestation) were randomised to receive 1 h FC-sIPPV followed by 1 h TC-sIPPV or the inverse shift, according to a computer-created randomisation table. Eligible babies had hyaline membrane disease and received 200 mg/kg surfactant at least 6 h before the study period. Respiratory mechanics, ventilatory and vital parameter data were registered real time. Results: FC-sIPPV resulted in lower-rate volume ratio, pressure × rate product, mean airway pressure and heart rate; tidal volume and oxygen saturation were higher (all p<0.001). Spontaneous inspiratory time was lower than usually set by the physician and it was directly correlated to birth weight (rho = 0.5, p = 0.001) and gestational age (rho = 0.32, p = 0.001). No differences were noticed in the mechanics and blood gas and vital parameters during the two study phases. Conclusions: FC-sIPPV may safely result in a better patient ventilator synchrony. Inspiratory time usually set in neonatal critical care is higher than that decided by the baby during spontaneous effort. This should be considered when establishing time-cycled ventilation.